Assessing the disunity of the European union over the refugee crisis - Agrizzi, Natasha (My University, 2018)
The European Union claims to be more integrated than ever where there exists unity in certain areas through a common market, a common currency, a common border however, there is no common policy on asylum to address the current and evolving refugee crisis. Increased conflicts in the Middle East and Africa have led to the influx of refugees and asylum seekers to the European Union. In explaining the disunity over the refugee crisis in the European Union, it is necessary to explore the factors which influence states responses to the refugee crisis and applying these factors to case studies analyzing those states supporting the reallocation of refugees and those states against the reallocation of refugees. This can be attributed to member states interest and power which play a fundamental role in furthering disunity in the European Union.
Masters research report Submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters in International Relations 2018
Keywords: Emigration and immigration; Forced migration; Refugees--Africa; Refugees--European Union countries